Beliefs and Blameworthiness - Jackson, Liz (Stance: an international undergraduate philosophy journal, 2019)
In this paper, I analyze epistemic blameworthiness. After presenting Michael Bergmann’s definition of epistemic blameworthiness, I argue that his definition is problematic because it does not have a control condition. I conclude by offering an improved definition of epistemic blameworthiness and defending this definition against potential counterexamples.